Programa de justiça restaurativa aplicado na escola - Santos, Mayta Lobo dos (2014)
Restorative justice presents itself as a mean to solve conflict, which aims not only at the accountability of the aggressor but also at his social reintegration. Its method requires the effective participation of all those involved, aggressor and victim. In this process, there can even be the contribution of third parties (involved or supporters), under the supervision of a facilitator. All the participants expose their reasons, feelings and suggestions as to the accountability of the offender and seek to satisfy their real needs stemming from the conflict. The restorative process takes place through previous and individualized interviews with the parties, in preparation for a general meeting in which the restorative agreement will be reached. As Restorative Justice has the values of inclusion, belonging, solidarity and active listening as its founding principles, we chose the school environment to begin implementation of a Restorative Justice Program because it is a place conducive to transformation. This work is the result of the preparation, implementation and evaluation of a restorative justice program in a public school in the metropolitan area of Curitiba - Paraná, with the objective of proposing to every individual in this environment a less violent communication, through the development of virtues. For that, there was the collaboration of a technical team consisting of psychologists, and the analysis of the behaviors of the students by means of the reports described in the record books from the educational department. After presenting the program to the school community, a committee was formed, coordinated by the researcher and composed by the technical staff and representatives of teachers, staff, administration, students and parents, in order to select cases for the program. Three cases were assigned, in which Pre- Circle, Circle and Post-Circle restorative meetings took place, which resulted in the preparation of three agreements and the proposal of concrete actions that promote the development of virtues, both in students involved in conflict, and in their parents, effected through the Moral Behavior Program and Parenting Practices Program. In addition, participants (offenders and victims) gave lectures in the school about the benefits of the Restorative Justice Program and, when necessary, were referred to remedial classes, which were the responsibility of the project team, and invited to participate in therapy with psychologists taking part in the program. A theater play on parenting practices was also presented to the school community. Finally, the involvement, commitment and changes, which took place during the implementation of the program, were evaluated in a three-month follow up period. The results showed that there were partial changes in the behavior of the students, who began adopting more appropriate practices, characterized, for example, by gentler and less violent acts, thus expanding their repertoire of conflict resolution. However, the new conduct did not maintain its initial intensity, seeing that the families, mainly those of the aggressors, did not become involved in the process.